Crédito e crescimento econômico: uma análise da relevância dos tipos de crédito no Brasil - Carla Michelle Coelho de Andrade (2009)
This paper aims to clarify the relationship between finance and economic growth with respect to the reality of Brazil, showing the intense regional disparities observed in its territory. This is an investigation about the influence of credit on the wealth production of the country, considering a new regional division, which cluster the municipalities according to similarities and dissimilarities concerning the social and economic characteristics. In forming these groups were used multivariate statistical methods that permited to propose in this study a peculiar typology of cities. Moreover, it was developed an empirical analysis (Panel Data: fixed effect) in order to investigate the relevance and to quantify the effects that each type of credit exert on the wealth generated in each municipal profile. The results pointed to the significant effects of certain credit categories on economic growth in some types of municipalities, wich are related to the especific levels of finance concession in cities, as well as to the socioeconomic characteristics of them.